Non-aqueous electrolyte and lithium ion battery
By using the cyclic unsaturated bond sulfate structure compound A in the nonaqueous electrolyte in the lithium-ion battery, a dual interface is formed, which solves the problem of insufficient cycling stability of the lithium-ion battery under high voltage, and significantly improves the high-temperature, cycling and low-temperature performance of the battery.
Patent Information
- Application Number
- CN202510015972.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-21
AI Technical Summary
In high-voltage application scenarios, existing lithium-ion batteries have problems such as insufficient cycling stability, performance attenuation, cationic mixed discharge and performance degradation in high-temperature environments.
A non-aqueous electrolyte containing compound A with a cyclic unsaturated bond sulfate structure is developed. This compound can polymerize at the interface of the negative electrode to form a polymerized protective layer, and forms an inorganic SEI interface rich in sulfur and nitrogen through O=S=O and nitrogen components on the ring to improve the lithium ion transmission rate.
By forming an inorganic and organic dual interface, the high-temperature, cycling and low-temperature performance of lithium-ion batteries is improved, and the cycling stability and storage performance of the battery at high voltages are improved.
Smart Images

Figure CN119674244A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy batteries, and in particular relates to a non-aqueous electrolyte and a lithium-ion battery. Background Art
[0002] With the rapid progress of global transportation and the clear goal of carbon neutrality, the electric vehicle (EV) industry has ushered in unprecedented development opportunities, which in turn has driven the urgent demand for high-performance lithium-ion batteries, especially the significant improvement in energy density and power density. At present, the mainstream technology trend of lithium-ion batteries for electric vehicles focuses on the combination of lithium nickel cobalt manganese oxide (NCM) ternary positive electrode materials and silicon-carbon composite negative electrodes. This combination effectively improves the energy and power output of the battery.
[0003] However, although NCM ternary cathode materials have significant advantages such as high cost-effectiveness and large specific capacity, they are also accompanied by a series of challenges, including insufficient stability under high-rate charge and discharge conditions, performance degradation during high-voltage cycles, cation mixing, and performance degradation under high-temperature environments. At the same time, silicon-carbon composite anode materials have become a research hotspot due to their high specific capacity, but they have huge volume changes (up to 300%) under high-voltage operation, which not only leads to frequent reconstruction of the interface between the electrode and the electrolyte, but also accelerates the consumption of the electrolyte, seriously affecting the long-term cycle stability and service life of the battery.
[0004] In order to overcome these difficulties, especially to improve the cycle life of lithium-ion batteries in high-voltage application scenarios, relevant personnel are working to optimize the chemical and structural design of batteries. Among them, optimizing the composition of the electrolyte to form a high-quality solid electrolyte interface film (SEI film) on the surface of the negative electrode has become one of the key strategies. The ideal SEI film should be dense, stable and able to effectively isolate the electrolyte from direct contact with the negative electrode active material, thereby significantly reducing the occurrence of side reactions, protecting the electrode material, reducing the formation of lithium dendrites, and ultimately improving the battery's cycle stability and storage performance at high voltage.
[0005] Therefore, there is an urgent need to develop new non-aqueous electrolytes to meet the market demand for use in high voltage application scenarios. Summary of the invention
[0006] The object of the present invention is to provide a non-aqueous electrolyte and a lithium ion battery, wherein the compound A contained in the non-aqueous electrolyte can form a SEI film with a fast lithium ion transmission rate and excellent interface stability, thereby improving the electrochemical performance of the lithium ion battery.
[0007] To achieve the above-mentioned purpose, the present invention provides a non-aqueous electrolyte, comprising an electrolyte salt, a non-aqueous organic solvent and an additive, wherein the additive comprises a compound A as shown in structural formula I or structural formula II, wherein X is C, O or N, R1 is selected from hydrogen, a substituted or unsubstituted C1~C6 hydrocarbon group, and R2 and R3 are each independently selected from hydrogen, a halogen, a substituted or unsubstituted C1~C6 hydrocarbon group.
[0008]
[0009] In the electrolyte of the present invention, the compound A shown in structural formula I or structural formula II has a cyclic unsaturated bond sulfate structure. During the initial formation process, the C=C double bond in the ring can polymerize at the negative electrode interface to form a polymerized protective layer to improve the high temperature and cycle performance of the battery. In addition, the presence of O=S=O and nitrogen components on the ring can form an inorganic SEI interface rich in sulfur and nitrogen, which has a better lithium ion transmission rate. Therefore, the compound A shown in structural formula I or structural formula II can form an inorganic and organic dual interface in the battery, thereby improving the high temperature, cycle and low temperature performance of the battery.
[0010] As a technical solution of the present invention, X is C or O, R1 is selected from hydrogen, halogen substituted or unsubstituted C1~C3 hydrocarbon group, and R2 and R3 are each independently selected from hydrogen, halogen, halogen substituted or unsubstituted C1~C3 hydrocarbon group.
[0011] As a technical solution of the present invention, the compound A is selected from at least one of compounds one to six.
[0012]
[0013]
[0014] As a technical solution of the present invention, based on the sum of the masses of the electrolyte salt, the non-aqueous organic solvent and the additive being 100%, the mass proportion of the compound A is 0.1-5.0%.
[0015] As a technical solution of the present invention, based on the sum of the masses of the electrolyte salt, the non-aqueous organic solvent and the additive being 100%, the mass proportion of the electrolyte salt is 10-25%.
[0016] As a technical solution of the present invention, the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium methane sulfonate, lithium trifluoromethyl sulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorophosphate, lithium difluorobis(oxalatophosphate) and 2-trifluoromethyl-4,5-dicyanoimidazole lithium.
[0017] As a technical solution of the present invention, based on the sum of the masses of the electrolyte salt, the non-aqueous organic solvent and the additive being 100%, the mass proportion of the non-aqueous organic solvent is 75-90%.
[0018] As a technical solution of the present invention, the non-aqueous organic solvent includes at least one of a carbonate compound, a carboxylate compound and an ether compound.
[0019] The second aspect of the present invention provides a lithium ion battery with a charging voltage of 4.45V, comprising a positive electrode material, a negative electrode material and the aforementioned non-aqueous electrolyte. The battery still has good electrochemical performance under a high voltage system.
[0020] As a technical solution of the present invention, the positive electrode material comprises lithium nickel cobalt manganese oxide, the lithium nickel The chemical formula of cobalt manganese oxide is LiNi x Co y Mn (1-x-y) M z O2, wherein 0.1≤x<0.9, x+y<1, 0≤z<0.08, M is at least one of Al, Mg, Zr and Ti, and the negative electrode material includes at least one of alkaline metals, carbon-based materials, silicon-based materials and tin-based materials. DETAILED DESCRIPTION
[0021] The lithium ion battery of the present invention still has better electrochemical performance under a high voltage system of 4.45V.
[0022] Lithium-ion batteries include positive electrode materials, negative electrode materials and non-aqueous electrolyte.
[0023] Among them, the positive electrode material includes lithium nickel cobalt manganese oxide, and the chemical formula of lithium nickel cobalt manganese oxide is LiNi x Co y Mn (1-x-y) M z O2, wherein 0.1≤x<0.9, x+y<1, 0≤z<0.08, and M is at least one of Al, Mg, Zr, and Ti. The negative electrode material includes at least one of an alkaline metal, a carbon-based material, a silicon-based material, and a tin-based material. The alkaline metal may include metallic lithium or a lithium alloy, and the lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy. The carbon-based material may include at least one of graphite, hard carbon, soft carbon, graphene, and mesophase carbon microspheres. The silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, and a silicon alloy material. The tin-based negative electrode may include at least one of elemental tin, tin carbon, tin oxide, and a tin alloy material.
[0024] The non-aqueous electrolyte includes an electrolyte salt, a non-aqueous organic solvent and an additive. Taking the sum of the mass of the electrolyte salt, the non-aqueous organic solvent and the additive as 100%, the mass proportion of the electrolyte salt is 10-25%. Preferably, the mass proportion of the electrolyte salt is 10-18%. As an example, the mass proportion of the electrolyte salt is 10%, 12%, 14%, 15%, 16%, 18%, 20%, 23%, 25%, and the content of the electrolyte salt is not limited to the listed values, and other values not listed in the numerical range are also applicable. The electrolyte salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiPO2F2), and lithium difluorobis(oxalatophosphate) (LiDFBP). The mass proportion of the non-aqueous organic solvent is 75-90%. Preferably, the mass proportion of the non-aqueous organic solvent is 80-88%. As an example, the mass proportion of the non-aqueous organic solvent is 75%, 77%, 79%, 80%, 82%, 84%, 86%, 88%, and 90%. The content of the non-aqueous organic solvent is not limited to the listed values, and other values not listed within the numerical range are also applicable. The non-aqueous organic solvent includes at least one of carbonate compounds, carboxylate compounds and ether compounds. Further, carbonate compounds include but are not limited to cyclic carbonates and / or chain carbonates, wherein cyclic carbonates may be but are not limited to ethylene carbonate (EC), propylene carbonate (PCA), and butylene carbonate (BC). Chain carbonates include but are not limited to dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and propylene carbonate (PC). Carboxylate compounds include but are not limited to cyclic carboxylates and / or chain carboxylates. Cyclic carboxylates may specifically include but are not limited to at least one of γ-butyrolactone (GBL), γ-valerolactone (GVL), and δ-valerolactone (DVL). Chain carboxylates include but are not limited to methyl acetate (MA), ethyl acetate (EA), propyl acetate (EP), butyl acetate (BAC), propyl propionate (PP), and butyl propionate (PRB). Ether compounds include cyclic ethers and / or chain ethers. The cyclic ether may specifically include, but is not limited to, at least one of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), and 2-trifluoromethyltetrahydrofuran (2-CF3-THF).The chain ethers may specifically include but are not limited to dimethoxymethane (DMM), diethoxymethane (DEM), ethoxymethoxymethane (DCE), ethylene glycol di-n-butyl ether (EDB), and diethylene glycol dimethyl ether (DEGME).
[0025] The additive includes a compound A as shown in structural formula I or structural formula II, wherein X is C, O or N, R1 is selected from hydrogen, substituted or unsubstituted C1~C6 hydrocarbon group, and R2 and R3 are each independently selected from hydrogen, halogen, substituted or unsubstituted C1~C6 hydrocarbon group.
[0026]
[0027] In R1 of compound A of the present invention, substituted or unsubstituted C1~C6 hydrocarbon groups refer to C1~C6 hydrocarbon groups substituted with no substituents or C1~C6 hydrocarbon groups substituted with substituents. Further, R1 is selected from hydrogen, C1~C3 alkyl, C2~C3 alkenyl, C2~C3 alkynyl, halogen-substituted C1~C3 alkyl, halogen-substituted C2~C3 alkenyl or halogen-substituted C2~C3 alkynyl. Halogen can be fluorine, chlorine, bromine, iodine, preferably fluorine. C1~C6 hydrocarbon groups refer to alkyl groups containing 1~6 carbon atoms, alkenyl groups containing 2~6 carbon atoms or alkynyl groups containing 2~6 carbon atoms. C1~C6 hydrocarbon groups can be, but are not limited to, methyl, ethyl, propyl, butyl, isopropyl, vinyl, propenyl, ethynyl, propynyl. Substituents refer to other atoms or groups that replace one or more hydrogen atoms in a hydrocarbon group. Substituents can be halogens (such as fluorine, chlorine, bromine, iodine), hydroxyl groups, amino groups, nitro groups, alkoxy groups, or aryl groups. For example, a methyl group can be replaced by a chlorine atom to form a chloromethyl group (-CH2Cl) or by a hydroxyl group to form a hydroxymethyl group (-CH2OH).
[0028] In R2 and R3 of compound A of the present invention, substituted or unsubstituted C1~C6 hydrocarbon groups refer to C1~C6 hydrocarbon groups substituted with no substituents or C1~C6 hydrocarbon groups substituted with substituents. Further, R2 and R3 are each independently selected from hydrogen, halogen, C1~C3 alkyl, C2~C3 alkenyl, C2~C3 alkynyl, halogen-substituted C1~C3 alkyl, halogen-substituted C2~C3 alkenyl or halogen-substituted C2~C3 alkynyl. Halogen can be fluorine, chlorine, bromine, iodine, preferably fluorine. C1~C6 hydrocarbon groups refer to alkyl groups containing 1~6 carbon atoms, alkenyl groups containing 2~6 carbon atoms or alkynyl groups containing 2~6 carbon atoms. C1~C6 hydrocarbon groups can be, but are not limited to, methyl, ethyl, propyl, butyl, isopropyl, vinyl, propenyl, ethynyl, propynyl. Substituents refer to other atoms or groups that replace one or more hydrogen atoms in a hydrocarbon group. Substituents can be halogens (such as fluorine, chlorine, bromine, iodine), hydroxyl groups, amino groups, nitro groups, alkoxy groups, or aryl groups. For example, a methyl group can be replaced by a chlorine atom to form a chloromethyl group (-CH2Cl) or by a hydroxyl group to form a hydroxymethyl group (-CH2OH).
[0029] Compound A is at least one selected from Compound 1 to Compound 6.
[0030]
[0031] CAS:912259-05-3CAS:54554-02-8CAS:111248-89-6
[0032] CAS:943594-65-8CAS:24827-66-5CAS:136061-95-5 The mass proportion of compound A is 0.1~5.0%. As an example, the mass proportion of compound A can be but is not limited to 0.1%, 0.2%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, and 5.0%. The content of compound A is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0034] If no specific conditions are specified in the examples and comparative examples, the experiments may be carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products available on the market.
[0035] Example 1 1.1 Preparation of electrolyte In a glove box filled with nitrogen (O2 <1ppm, H2O <1ppm), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and ethyl acetate (EA) were mixed in a mass ratio of 2:2:2:1 to obtain a mixed solvent as an organic solvent, and compound A was added to obtain a mixed solution. The mixed solution was sealed and packaged and placed in a quick freezer (-4°C) for 2 hours, then taken out, and in a glove box filled with nitrogen (O2 <1ppm, H2O <1ppm), electrolyte salt was slowly added to the mixed solution, and the electrolyte was obtained after mixing evenly.
[0036] 1.2 Preparation of positive electrode The ternary material LiNi 0.5 Co 0.2 Mn 0.3 Zr 0.03 O2, conductive agent SuperP, adhesive PVDF and carbon nanotubes (CNT) are mixed evenly in a mass ratio of 96.5:1.5:1:1 to form a lithium-ion battery positive electrode slurry with a certain viscosity, which is coated on the aluminum foil for current collector. The coating amount is 324g / m 2 , dried at 85°C and then cold pressed; then trimmed, cut into pieces, and slit, and after slitting, dried at 85°C for 4 hours under vacuum conditions, and the tabs were welded to make lithium-ion battery positive electrodes that meet the requirements.
[0037] 1.3 Preparation of negative electrode Artificial graphite and silicon oxide are mixed in a mass ratio of 90:10, and then mixed with conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber emulsion) in a mass ratio of 95:1.5:1.0:2.5 to make a slurry, mix evenly, apply the mixed slurry on both sides of the copper foil, dry and roll to obtain a negative electrode sheet, and make a lithium-ion battery negative electrode sheet that meets the requirements. 1.4 Preparation of lithium-ion batteries The positive electrode sheet, negative electrode sheet and separator prepared according to the above process are laminated to form a lithium-ion battery with a thickness of 4.7mm, a width of 55mm and a length of 60mm. The battery is vacuum-baked at 75°C for 10h and the above electrolyte is injected. After standing for 24h, the battery is charged to 4.45V with a constant current of 0.1C (180mA), and then charged at a constant voltage of 4.45V until the current drops to 0.05C (90mA); then discharged to 3.0V with 0.2C (180mA), and the charge and discharge are repeated twice. Finally, the battery is charged to 3.8V with 0.2C (180mA) to complete the production of the lithium-ion battery.
[0038] The components and contents of the electrolytes of Examples 1 to 14 and Comparative Examples 1 to 2 are shown in Table 1, wherein the preparation processes of the lithium ion battery electrolytes, positive electrode sheets, negative electrode sheets, and lithium ion batteries of Examples 2 to 14 and Comparative Examples 1 to 2 are the same as those of Example 1.
[0039] Table 1 Compositions of the electrolytes of the examples and comparative examples
[0040]
[0041] The lithium ion batteries prepared in Examples 1 to 14 and Comparative Examples 1 to 2 were subjected to high temperature cycle performance tests, room temperature cycle performance tests, and low temperature and fast charging performance tests under the following conditions. The results are shown in Table 2.
[0042] (1) Normal temperature cycle performance test At room temperature (25°C), the lithium-ion battery is charged and discharged once at 1.0C / 1.0C (the battery discharge capacity is C0) with an upper voltage of 4.45V. Then, it is charged and discharged at 1.0C / 1.0C for 500 cycles at room temperature (the battery discharge capacity is C1), and the capacity retention rate is calculated.
[0043] Capacity retention rate = (C1 / C0)*100% (2) High temperature cycle test Under high temperature (45°C) conditions, the lithium-ion battery is charged and discharged at 1.0C / 1.0C once (the battery discharge capacity is C0) with an upper voltage of 4.45V, and then charged and discharged at 1.0C / 1.0C for 400 cycles (the battery discharge capacity is C1) under high temperature (45°C) conditions, and the capacity retention rate is calculated.
[0044] Capacity retention rate = (C1 / C0)*100% (3) Room temperature fast charging performance test At room temperature (25°C), the lithium-ion battery is charged and discharged at 1.0C / 1.0C once (the battery discharge capacity is C0) with an upper voltage of 4.45V. Then, it is charged and discharged at 4.0C / 1.0C for 500 cycles at room temperature (the battery discharge capacity is C1), and the capacity retention rate is calculated.
[0045] Capacity retention rate = (C1 / C0)*100% (4) High temperature fast charging performance test Under high temperature (45°C) conditions, the lithium-ion battery is charged and discharged at 1.0C / 1.0C once (the battery discharge capacity is C0) with an upper voltage of 4.45V. Then, it is charged and discharged at 4.0C / 1.0C for 400 cycles at room temperature (the battery discharge capacity is C1), and the capacity retention rate is calculated.
[0046] Capacity retention rate = (C1 / C0)*100% (5) Low temperature performance test At room temperature (25°C), the lithium-ion battery is charged and discharged at 0.5C / 0.5 (battery cut-off voltage is 3.0V, discharge capacity is C0), and the upper limit voltage is 4.45V (cut-off current 0.05C). Then the battery is fully charged to 4.45V (cut-off current 0.05C) at 0.5C at room temperature (25°C), and then the battery is transferred to -20°C and left for 4h, and discharged to 3.0V at 0.5C, and the discharge capacity is C1. The capacity retention rate is calculated.
[0047] Capacity retention rate = (C1 / C0) * 100% Table 2 Test results of lithium-ion battery performance of various embodiments and comparative examples
[0048] From the results in Table 2, it can be seen that the electrochemical comprehensive performance of the lithium-ion batteries of Examples 1 to 14 is better, which is because Examples 1 to 14 include compound A. Compound A has a cyclic unsaturated bond sulfate structure. During the initial formation process, the C=C double bond in the ring can polymerize at the negative electrode interface to form a polymerized protective layer to improve the high temperature and cycle performance of the battery. In addition, the presence of O=S=O and nitrogen components on the ring can form an inorganic SEI interface rich in sulfur and nitrogen, which has a better lithium ion transmission rate. Therefore, compound A can form an inorganic and organic dual interface in the battery, thereby improving the high temperature, cycle and low temperature performance of the battery.
[0049] Although Comparative Example 2 contains an intracyclic unsaturated bond and an O=S=O structure, the performance of the inorganic interface film formed by sulfur alone is poor, and the lithium ion transmission rate is average, especially under a high voltage system of 4.45V, its fast charging and low temperature performance are poor.
[0050] Comparing Examples 1 to 6, it can be seen that when compound A is compound VI, the high temperature, cycle and low temperature performance of the lithium-ion battery are better. This is because compound VI contains an N-CH3 structure, which has a lower reaction activity than NH, consumes less active lithium, and the battery capacity is relatively higher. In addition, the SEI formed by the N-CH3 structure has larger holes, and lithium ions are more easily deintercalated at low temperatures. The OS=O structure in compound VI can form an inorganic SEI component with lower impedance, improving the high temperature stability and low temperature discharge capability of the electrode electrolyte interface.
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A non-aqueous electrolyte comprising an electrolyte salt, a non-aqueous organic solvent and an additive, wherein the additive comprises a compound A as shown in structural formula I or structural formula II, wherein: X is C, O or N, R1 is selected from hydrogen, substituted or unsubstituted C1~C6 hydrocarbon group, R2 and R3 are each independently selected from hydrogen, halogen, substituted or unsubstituted C1~C6 hydrocarbon group, 。 2. The non-aqueous electrolyte according to claim 1, characterized in that X is C or O, R1 is selected from hydrogen, halogen substituted or unsubstituted C1~C3 hydrocarbon group, and R2 and R3 are each independently selected from hydrogen, halogen, halogen substituted or unsubstituted C1~C3 hydrocarbon group.
3. The non-aqueous electrolyte according to claim 1, characterized in that The compound A is selected from at least one of compounds 1 to 6, 。 4. The non-aqueous electrolyte according to claim 1, characterized in that Based on the sum of the mass of the electrolyte salt, the non-aqueous organic solvent and the additive being 100%, the mass proportion of the compound A is 0.1-5.0%.
5. The nonaqueous electrolyte according to claim 1, characterized in that Based on the sum of the mass of the electrolyte salt, the nonaqueous organic solvent and the additive being 100%, the mass of the electrolyte salt accounts for 10-25%.
6. The non-aqueous electrolyte according to claim 1, characterized in that The electrolyte salt includes at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylsulfonyl imide, lithium methane sulfonate, lithium trifluoromethyl sulfonate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium difluorobisoxalatophosphate, and lithium 2-trifluoromethyl-4,5-dicyanoimidazole.
7. The nonaqueous electrolyte according to claim 1, characterized in that Taking the sum of the mass of the electrolyte salt, the non-aqueous organic solvent and the additive as 100%, the mass of the non-aqueous organic solvent accounts for 75-90%.
8. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous organic solvent includes at least one of a carbonate compound, a carboxylate compound and an ether compound.
9. A lithium ion battery, characterized in that: The charging voltage is 4.45V, and the battery comprises a positive electrode material, a negative electrode material and the non-aqueous electrolyte according to any one of claims 1 to 8.
10. The lithium ion battery according to claim 9, characterized in that: The positive electrode material includes Lithium nickel cobalt manganese oxide, the chemical formula of the lithium nickel cobalt manganese oxide is LiNi x Co y Mn (1-x-y) M z O2, wherein 0.1≤x<0.9, x+y<1, 0≤z<0.08, M is at least one of Al, Mg, Zr and Ti, and the negative electrode material includes at least one of alkaline metals, carbon-based materials, silicon-based materials and tin-based materials.
Citation Information
Cited By
Electrolyte additive, electrolyte and electrochemical device
CN120904132A